Shift kerja dan burnout perawat di unit pediatric: Studi kasus analitis - Andiny, Aliya Nuri; Asmaningrum, Nurfika; Purwandari, Retno; Suparman, Maman; Listyaningrum, Desy; Wibowo, Suhendra Agung (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Burnout is a critical occupational issue among nurses, affecting their well-being and the quality of patient care. It is characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment. Nurses working rotating or night shifts are particularly vulnerable due to high workload and limited recovery time. Purpose: To examine burnout levels among nurses. Method: A descriptive quantitative design was used, involving nurses on morning, afternoon, and night shifts. Data were collected using the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) and analyzed to determine overall burnout and its dimensions across shifts. Results: 53.3% of respondents experienced burnout, while 46.7% did not. Most nurses across all shifts exhibited moderate levels of burnout. Emotional exhaustion was the most dominant dimension, followed by depersonalization, which was higher among nurses on rotational shifts or in understaffed units. Personal accomplishment remained high for morning and afternoon shifts, but moderated for night shifts, indicating a negative effect of shift instability on perceived professional competence. Conclusion: Burnout is prevalent among nurses with varying impacts across its dimensions. Interventions that target emotional exhaustion, increase personal accomplishment, and reduce depersonalization, particularly for night and rotating shift nurses, are crucial for supporting nurse well-being and maintaining quality of care. Keywords: Burnout Levels; Nurse; Work Shift. Pendahuluan: Burnout merupakan masalah pekerjaan yang kritis di kalangan perawat, yang memengaruhi kesejahteraan mereka dan kualitas perawatan pasien. Burnout ditandai dengan kelelahan emosional, depersonalisasi, dan penurunan pencapaian pribadi. Perawat yang bekerja dengan sistem rotasi atau shift malam sangat rentan karena beban kerja yang tinggi dan waktu pemulihan yang terbatas. Tujuan: Untuk meneliti tingkat burnout di kalangan perawat. Metode: Desain kuantitatif deskriptif digunakan, yang melibatkan perawat pada shift pagi, siang, dan malam. Data dikumpulkan menggunakan Maslach Burnout Inventory-Human Services Survey (MBI-HSS) dan dianalisis untuk menentukan burnout secara keseluruhan dan dimensinya di seluruh shift. Hasil: Sebanyak 53.3% responden mengalami burnout, sedangkan 46.7% tidak. Sebagian besar perawat di semua shift menunjukkan burnout tingkat sedang. Kelelahan emosional merupakan dimensi yang paling dominan, diikuti oleh depersonalisasi yang lebih tinggi di antara perawat dengan sistem rotasi atau di unit yang kekurangan staf. Pencapaian pribadi tetap tinggi untuk shift pagi dan siang, tetapi moderat untuk shift malam, menunjukkan efek negatif dari ketidakstabilan shift terhadap kompetensi profesional yang dirasakan. Simpulan: Burnout lazim terjadi di kalangan perawat dengan dampak yang bervariasi pada dimensinya. Intervensi yang menargetkan kelelahan emosional, meningkatkan pencapaian pribadi, dan mengurangi depersonalisasi, terutama untuk perawat shift malam dan shift bergilir, sangat penting untuk mendukung kesejahteraan perawat dan menjaga kualitas perawatan. Kata Kunci: Burnout; Perawat; Shift Kerja.